Inquiry Learning Model at SMK Negeri 6 Masni District, West Papua Year of Study 2021/2022 - Juni Ernawati Manjorang (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2021)
This study aims to improve learning outcomes for class XI ATPH through the application of the Inquiry Learning Model in the productive subject of Vegetable Crops Agribusiness at SMK (Vocational Upper-Seconday School) Negeri 6 Masni District. Through the Inquiry Learning Model, students are expected to achieve the goal of improved learning outcomes of Productive Vegetable Crops Agribusiness. This research is a Classroom Action Research (CAR) which is carried out in a two-stage offline learning cycle. Each cycle consists of four stages, namely planning, action implementation, observation, and reflection. The subjects in this study are 28 students from the class XI ATPH SMK Negeri 6 Masni. The success indicator in this study is: 75% of the students are actively involved in the learning process, an increase in learning outcomes is achieved during each cycle through the post-test, and 75% of the students are able to achieve the Minimum Completeness Criteria (KKM) determined by the school, which is 70.